Influence of Substrates on the Surface Characteristics and Membrane Proteome of Fibrobacter succinogenes S85 - Raut, Mahendra P. (PLoS One, 2015)
Although Fibrobacter succinogenes S85 is one of the most proficient cellulose degrading bacteria among all mesophilic organisms in the rumen of herbivores, the molecular mechanism behind cellulose degradation by this bacterium is not fully elucidated. Previous studies have indicated that cell surface proteins might play a role in adhesion to and subsequent degradation of cellulose in this bacterium. It has also been suggested that cellulose degradation machinery on the surface may be selectively expressed in response to the presence of cellulose. Based on the genome sequence, several models of cellulose degradation have been suggested. The aim of this study is to evaluate the role of the cell envelope proteins in adhesion to cellulose and to gain a better understanding of the subsequent cellulose degradation mechanism in this bacterium. Comparative analysis of the surface (exposed outer membrane) chemistry of the cells grown in glucose, acid-swollen cellulose and microcrystalline cellulose using physico-chemical characterisation techniques such as electrophoretic mobility analysis, microbial adhesion to hydrocarbons assay and Fourier transform infra-red spectroscopy, suggest that adhesion to cellulose is a consequence of an increase in protein display and a concomitant reduction in the cell surface polysaccharides in the presence of cellulose. In order to gain further understanding of the molecular mechanism of cellulose degradation in this bacterium, the cell envelope-associated proteins were enriched using affinity purification and identified by tandem mass spectrometry. In total, 185 cell envelope-associated proteins were confidently identified. Of these, 25 proteins are predicted to be involved in cellulose adhesion and degradation, and 43 proteins are involved in solute transport and energy generation. Our results supports the model that cellulose degradation in F. succinogenes occurs at the outer membrane with active transport of cellodextrins across for further metabolism of cellodextrins to glucose in the periplasmic space and inner cytoplasmic membrane.